PENGARUH HASIL BELAJAR AKUNTANSI PERUSAHAAN JASA DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SPREADSHEET SISWA KELAS X DAN XI AKUNTANSI DI SMK KANSAI PEKANBARU - Lestari, Erna; ', Sumarno; Trisnawati, Fenny (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aims to know the influence the achievement learning accounting services company and learning motivation on achievment learning spreadsheet class X and XI accounting in Kansai SMK Pekan Baru. The population in this research is the accounting skills program students of class X and XI with a total of 66 students, and all students become subjects of research, so this research is the research population. Measurement data using questionnairs and documentation. Data analysis used is multiple linear regression. Research result shows the achievement learning accounting services company and learneing motivation on learning achievement spreadsheet class X and XI accounting in Kansai SMK Pekan Baru. Aqual influence achievement learning accounting services company of 0.523, and learneing motivation of 0,210. Judging from the calculation of R2 (R Square Change) obtained the value of 0.439.this means that the percentage of contribution of achievment learning accounting service company and learning motivation on learning achievment spreadsheet variable 43,9%.Keyword : Achievement Learning Accounting Services Company, Learning Motivation, Achievement Learning Spreadsheet